Trajetória de vida profissional no percurso acadêmico: desafios e superações - Silva, Erimar Rosalino da (Brasil, 2024)
This Final Course Work (FCW) aims to report the remarkable experiences of my life trajectory in Basic Education, personal, professional and academic, with memories of childhood, the first contact with school, through the professional experiences acquired, until entering the Federal University of Amazonas - UFAM, this event being the beginning of the realization of the dream of attending Higher Education, since, given the financial difficulties, until then, it was just a distant dream. It also contemplates the process of building knowledge during the period of teacher training, as well as the expectations, challenges, frustrations and victories experienced in this academic trajectory. Among other important points of teacher training, this memorial aims to reflect on the importance of supervised internships in teacher training, reading and writing, and games in the teaching and learning process. It is autobiographical material, configuring itself as a narrative that is simultaneously historical and reflective. Here, therefore, the facts and events that constituted the author's professional academic career will be reported, so that the reader can have complete and accurate information about the itinerary taken.